2017
DOI: 10.1021/acs.jmedchem.7b00621
|View full text |Cite
|
Sign up to set email alerts
|

Benzoxaborole Antimalarial Agents. Part 5. Lead Optimization of Novel Amide Pyrazinyloxy Benzoxaboroles and Identification of a Preclinical Candidate

Abstract: Carboxamide pyrazinyloxy benzoxaboroles were investigated with the goal to identify a molecule with satisfactory antimalarial activity, physicochemical properties, pharmacokinetic profile, in vivo efficacy, and safety profile. This optimization effort discovered 46, which met our target candidate profile. Compound 46 had excellent activity against cultured Plasmodium falciparum, and in vivo against P. falciparum and P. berghei in infected mice. It exhibited good PK properties in mice, rats, and dogs. It was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…To investigate the possible link between splicing inhibition and the methylated metabolites, we measured the effects of the chosen compounds on splicing. We also included AN2965 ( Fig 1 ), the compound whose mode of action had been investigated previously [ 22 ], and the antimalarial candidate AN13762 ( Fig 1 , compound 46 in [ 25 ]). Initial triplicate measurements ( Fig 7A , experiment 1) gave reproducible results for most of the compounds; repeat assays for three that had given ambiguous results confirmed that they gave substantially less splicing inhibition than AN7973 ( Fig 7 , experiment 2 and S4A Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the possible link between splicing inhibition and the methylated metabolites, we measured the effects of the chosen compounds on splicing. We also included AN2965 ( Fig 1 ), the compound whose mode of action had been investigated previously [ 22 ], and the antimalarial candidate AN13762 ( Fig 1 , compound 46 in [ 25 ]). Initial triplicate measurements ( Fig 7A , experiment 1) gave reproducible results for most of the compounds; repeat assays for three that had given ambiguous results confirmed that they gave substantially less splicing inhibition than AN7973 ( Fig 7 , experiment 2 and S4A Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Various oxaboroles are being considered for treatment of apicomplexan parasites; and AN13762 ( Fig 1 ) is in development [ 24 , 25 ]. Plasmodium and Toxoplasma that were resistant to AN3661 ( Fig 1 ) had mutations in the cleavage and polyadenylation factor CPSF3 [ 26 , 27 ], which is implicated in 3' cleavage of mRNA precursors prior to polyadenylation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2] The significance of these motifs can also be recognized from their presence in natural products, [3] pharmaceuticals, [4] polymers, [5] and their advanced application as versatile building blocks in protein and peptide chemistry. [6,7] Molecules with anilide moieties are recognized as antipyretic, [8] antimalarial, [9] antiinflammatory, [10] and antitumor [11] agents. Recent data gathered by medicinal chemists disclosed that in modern pharmaceuticals, the most frequently used methods for N-acylation rely on the reaction between amines and activated carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium parasites, which cause malaria, are members of the phylum Apicomplexa, and are therefore genetically related to Cryptosporidium parasites. Given this and the recent identification of benzoxaboroles with potent antimalarial activity 28,30,31 , we screened a library of benzoxaborole compounds for anticryptosporidial activity. Here, we report identification of a novel drug candidate, AN7973, for treatment of cryptosporidiosis.…”
mentioning
confidence: 99%